A review of functionality assessment scales in schizophrenia - Ifteni, Petru; Miron, Ana Aliana; Petric, Paula Simina; Teodorescu, Andreea; Manea, Mihnea Costin (Frontiers in Psychiatry, 2025)
IntroductionSchizophrenia is a severe and chronic psychiatric disorder marked by a complex and heterogeneous array of symptoms, including positive symptoms (such as hallucinations and delusions), negative symptoms (such as emotional blunting and social withdrawal), and cognitive deficits. These symptoms result in profound and persistent impairments across multiple domains of functioning, including self-care, interpersonal relationships, family life, and occupational performance. Therefore, evaluation of functionality in schizophrenia has become an important objective for monitoring the clinical and therapeutic outcome of the patients.MethodsThis review identifies and evaluates the development and use of functioning assessment scales in schizophrenia from 1976 to 2024. A comprehensive search of four major medical databases (PubMed, NIH, Wiley Online Library, and Springer Nature Link) covering studies published over nearly five decades yielded 42 distinct instruments that met predefined inclusion criteria. ResultsEach scale was examined in terms of its clinical utility, psychometric robustness, domains assessed, and the extent to which it integrates the perspectives of patients, clinicians, and caregivers. The analysis revealed a wide variation in the domains covered by these tools, many focusing heavily on either clinical or social aspects of functioning, often neglecting others such as occupational or familial roles. Additionally, the usability of several instruments in routine clinical settings was limited by their length or complexity. DiscussionsThese findings underscore the need for more streamlined, multidimensional, and user-friendly assessment tools that are both scientifically rigorous and practically applicable. The review highlights the importance of adopting a holistic approach to functional recovery in schizophrenia—one that considers not only symptom reduction but also quality of life and reintegration into the community. Future scale development should prioritize the inclusion of input from all key stakeholders and aim to capture the nuanced realities of daily functioning in individuals living with schizophrenia.